GOVERNMENT-LED INITIATIVES IN MALAYSIA-QATAR RELATIONS DURING MAHATHIR’S LEADERSHIP, 2018-2020 - Ismail, Norafidah; Osman, Nazariah; Nanaa, Alhussein (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The bilateral relationship between Malaysia and Qatar, established on strong economic foundations and a resilient policy of non-alignment, faced a critical juncture following the 2017 Gulf Crisis and subsequent Malaysian leadership change. This article examines the government-led initiatives undertaken by the Malaysian administration under Tun Mahathir Mohamad (2018–2020) to translate political commitment into tangible, institutionalised, and deepened bilateral relations. The study aims to detail the trajectory of close political and economic engagement, specifically focusing on high-level diplomacy and governmental efforts to formalise cooperation. This includes analysing reciprocal visits, such as Deputy Prime Minister Wan Azizah Wan Ismail’s 2018 visit to Qatar and the Emir of Qatar’s visit to Kuala Lumpur later that year, which featured the inauguration of an anti-corruption monument. Furthermore, the article assesses the institutionalisation of economic ties, notably the establishment of the Malaysia-Qatar Joint Business Council (MQJBC) in 2020 and the Memorandum of Understanding (MoU) between MIDA and IPAQ. The research uses desk research (secondary source research), involving collection of pre-existing data from various sources. The findings show the importance of state-led business diplomacy in positioning Malaysia as ASEAN’s gateway for Qatari investors and improving trade, which grew significantly between 2017-2018. These findings are examined through the Middle Power concept.